Preliminary evidence that fatigue contributes to anhedonia in stable individuals diagnosed with schizophrenia - Laraki, Yasmine; Bayard, Sophie; Decombe, Amandine; Capdevielle, Delphine; Raffard, Stéphane (Frontiers in Psychiatry, 2023)
Objectives Anhedonia and fatigue are trans-diagnostic symptoms commonly observed in schizophrenia. Anhedonia is a core negative symptom with a strong relationship with depression and is associated with diminished global functioning. Similarly, fatigue is also associated to depression and research across psychiatric illnesses indicate that fatigue may persist even when primary symptoms are treated. Although fatigue is common in people diagnosed with schizophrenia, it is under studied within this population. The objective of this exploratory study was to investigate the association of fatigue and anhedonia by controlling for depression in a sample of individuals diagnosed with schizophrenia. Method Fifty-one stable individuals diagnosed with schizophrenia from the University Department of Adult Psychiatry in Montpellier took part in this study. Participants completed questionnaires on fatigue impact and depression, and were assessed for symptom severity. Following data collection, statistical analyses were conducted in order to explore associations between clinical variables and fatigue impact. Based on the results obtained, a hierarchical linear regression was conducted in order to investigate whether fatigue impact contributed to the variance of negative symptoms. Results The hierarchical linear regression indicated that when controlling for depression, fatigue impact contributes to 20% of the variance of anhedonia. Together the social impact of fatigue and depression contribute to 24% of the variation of anhedonia. Conclusion To the best of our knowledge, this exploratory study is the first to investigate and show that fatigue impact may contribute to anhedonia. We recommend further research to investigate fatigue, its impact on symptomatology, and better categorization of negative symptoms in hopes of developing targeted fatigue treatment interventions.